Ionic strength of the equilibrium solution upon arsenic adsorption in Brazilian Oxisols - Campos, Mari Lucia; Guilherme, Luiz Roberto Guimarães; Visiolli, Elton; Antines, Alessandra Silveira; Curi, Nilton; Marques, João José; Silva, Marx Leandro Naves (Pesquisa Agropecuaria Brasileira, 2006)
The objective of this work was to evaluate the effect of ionic strength of the equilibrium solution on adsorption and desorption of arsenic, in 17 Oxisols of different Brazilian geographic regions. Arsenic adsorption was evaluated at two values of ionic strength (15 and 150 mmol L-1), two doses of As (15 and 150 mmol L-1), soil:solution ratio of 1:100 and pH 5.5. There were no differences in percentages of adsorption between the values of ionic strength 15 and 150 mmol L-1 (63.51 and 64.46%). Desorption percentage at the dose 15 mmol L-1 was smaller than 15% at the two values of ionic strength, except for LVd4 and LAd1, in which the desorption percentage was higher than 20%.